Exponential attractor for the Cahn-Hilliard-Oono equation in R^N - Cholewa, Jan W.; Czaja, Radosław (Topological Methods in Nonlinear Analysis, 2023)
We consider the Cahn-Hilliard-Oono equation in the whole of $\mathbb{R}^N$, $N≤ 3$.We prove the existence of an exponential attractor in $H^1\big(\mathbb{R}^N\big)$,which contains a global attractor. We also estimate from above fractal dimension of the attractors.